Death on the shelf - Brook, Allison (Brook, Allison. Haunted library mystery., 2021)
"Clover Ridge librarian Carrie Singleton investigates after her best friend's cousin's flirtatious husband is found dead in a chocolate fountain at an elaborate bridal shower"--